Case Study: Deep Breathing Relaxation Intervention to Reduce Pain in Post Sectio Caesarea Client - Elis Roslianti; Anisa Azmi; Wulan Permatasari; Nur Hidayat; Lilis Lismayanti (Genius Journal, 2022)
Objective: To determine the implementation of deep breathing relaxation techniques in clients with post operative section caesarea. Method: The method used is descriptive qualitative with a case study approach using nursing care that refers to the SDKI and SIKI books. The subject in this study was 1 sectio caesarea client with a diagnosis of acute pain who was treated in Teratai Room 2 BLUD Banjar City General Hospital. The data collection techniques included interviews, observations, physical examinations and documentation. Result: From nursing care for postoperative sectio caesarea clients, the symptoms that appear during the assessment are pain in the lower abdomen. The nursing problem that arises is acute pain related to physical injury agents referring to the SDKI book. Interventions carried out to reduce pain are deep breathing relaxation techniques. During the intervention process, the action went smoothly until the evaluation. In this study, there was a decrease in the pain scale from 3 to 0. Conclusion: After the intervention of breathing relaxation techniques on the client's pain scale was reduced from 3 to 0, while the subjective data from the anamnesis results, the client said the pain was reduced.